Transcriptomic Profiling of Buffalo Spermatozoa Reveals Dysregulation of Functionally Relevant mRNAs in Low-Fertile Bulls - Paul, Nilendu; Kumaresan, Arumugam; Das Gupta, Mohua; Nag, Pradeep; Guvvala, Pushpa Rani; Kuntareddi, Channareddi; Sharma, Ankur; Selvaraju, Sellappan; Datta, Tirtha Kumar (Frontiers in Veterinary Science, 2021)
Although, it is known that spermatozoa harbour a variety of RNAs that may influence embryonic development, little is understood about sperm transcriptomic differences in relation to fertility, especially in buffaloes. In the present study, we compared the differences in sperm functional attributes and transcriptomic profile between high- and low-fertile buffalo bulls. Sperm membrane and acrosomal integrity were lower (P<0.05) while protamine deficiency and lipid peroxidation were higher (P<0.05) in low- compared to high-fertile bulls. Transcriptomic analysis using mRNA microarray technology detected a total of 51282 transcripts in buffalo spermatozoa, of which 4050 transcripts were differentially expressed and 709 transcripts were found to be significantly dysregulated (P<0.05 and fold change >1) between high- and low-fertile bulls. Majority of the dysregulated transcripts were related to binding-activity, transcription, translation and metabolic processes with primary localization in cell nucleus, nucleoplasm and in cytosol. Pathways related to MAPK signalling, ribosome pathway and oxidative phosphorylation were dysregulated in low-fertile bull spermatozoa. Using bioinformatics analysis, we observed that several genes related to sperm functional attributes were significantly downregulated in low fertile bull spermatozoa. Validation of the results of microarray analysis was carried out using Real-time qPCR expression analysis of selected genes (YBX1, ORAI3 and TFAP2C). The relative expression of these genes followed the same trend in both the techniques. Collectively, this is the first study to report the transcriptomic profile of buffalo spermatozoa and to demonstrate the dysregulation of functionally relevant transcripts in low-fertile bull spermatozoa. The results of the present study opens up new avenues for understanding the aetiology for poor fertility in buffalo bulls and to identify fertility biomarkers.